A call to ARMS: targeting the PAX3-FOXO1 gene in alveolar rhabdomyosarcoma. (June 2013) - Olanich, Mary E; Barr, Frederic G
<x xml:space="preserve">Abstract</x> Introduction: Expression of fusion oncoproteins generated by recurrent chromosomal translocations represents a major tumorigenic mechanism characteristic of multiple cancers, including one-third of all sarcomas. Oncogenic fusion genes provide novel targets for therapeutic intervention. The PAX3-FOXO1 oncoprotein in alveolar rhabdomyosarcoma (ARMS) is presented as a paradigm to examine therapeutic strategies for targeting sarcoma-associated fusion genes. Areas covered: This review discusses the role of PAX3-FOXO1 in ARMS tumors. Besides evaluating various approaches to molecularly target PAX3-FOXO1 itself, this review highlights therapeutically attractive downstream genes activated by PAX3-FOXO1. Expert opinion: Oncogenic fusion proteins represent desirable therapeutic targets because their expression is specific to tumor cells, but these fusions generally characterize rare malignancies. Full development and testing of potential drugs targeted to these fusions are complicated by the small numbers of patients in these disease categories. Although efforts to develop targeted therapies against fusion proteins should continue, molecular targets that are applicable to a broader tumor landscape should be pursued. A shift of the traditional paradigm to view therapeutic intervention as target-specific rather than tumor-specific will help to circumvent the challenges posed by rare tumors and maximize the possibility of developing successful new treatments for patients with these rare translocation-associated sarcomas.